2012
DOI: 10.3402/ijch.v71i0.18833
|View full text |Cite
|
Sign up to set email alerts
|

Translational research to reducetrans-fat intakes in Northern Québec (Nunavik) Inuit communities: a success story?

Abstract: Following our results, based on population studies conducted in Greenland and Northern Canada, that Nunavik Inuit were thrice as highly exposed to dietary trans -fat as were Greenlandic Inuit, and that the biological levels found in Nunavik were already associated with deleterious blood lipid profiles, we decided to engage in translational activities. Our goal was to support Inuit communities in the practical implementation of a reduction of the trans -fat content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 15 publications
(15 reference statements)
0
28
0
Order By: Relevance
“…All studies indicated the necessity of community involvement (29.4%) ( 46 , 50 , 55 , 56 , 76 ), importance of context (29.4%) ( 45 , 47 , 49 , 53 , 54 ), or both (41.2%) ( 31 , 48 , 51 , 52 , 57 , 75 , 77 ) for successful KT in Inuit communities in the Circumpolar North ( Fig. 4 b).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…All studies indicated the necessity of community involvement (29.4%) ( 46 , 50 , 55 , 56 , 76 ), importance of context (29.4%) ( 45 , 47 , 49 , 53 , 54 ), or both (41.2%) ( 31 , 48 , 51 , 52 , 57 , 75 , 77 ) for successful KT in Inuit communities in the Circumpolar North ( Fig. 4 b).…”
Section: Resultsmentioning
confidence: 96%
“… Bar graph indicating the knowledge translation (KT) methods that were assessed in the literature including workshops ( 53 , 54 , 73 , 77 ), stakeholder meetings ( 50 , 51 , 53 , 75 ), written material ( 50 , 53 , 54 , 75 ), presentations ( 50 , 57 , 75 , 76 ), open houses ( 52 , 54 , 55 , 57 ), radio broadcasts ( 50 , 53 , 57 ), digital video ( 46 ), community of interest groups ( 47 ), television broadcasts ( 53 ), household visits ( 75 ) and immediate individual feedback (categories are not mutually exclusive) ( 76 ). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations